24‐4: Research on Water Vapor Penetration of OLED Encapsulation. Issue 1 (28th June 2021) - Sun, Tao; Qin, Chengjie; Wang, Tao; Zhang, Ziyu; Wang, Youwei; Zhang, Song; Liu, Zheng; Shi, Shiming; Wang, Dawei
Abstract : This paper studied the characteristics of OLED encapsulation film, the test method of water vapor penetration and improving the ability of water vapor barrier. It was found that the group changes after hygroscopic, transferred to Si‐O bond. Based on this mechanism, the test method of water vapor penetration was studied. The average water vapor penetration rate P of film A and film B was about 0.14nm/h and 34nm/h respectively at 85 °C /85%RH environment by TOF‐SIMS and XPS test. At the same time, the permeability lag phenomenon was found. The enhancement effect of inter‐layer structure on water vapor barrier ability was further studied.